PENGARUH GAYA KEPEMIMPINAN, PENGEMBANGAN SUMBER DAYA MANUSIA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI SULAWESI TENGAH - Maria, Agustin (Katalogis, 2013)
This research aims to know and analyze the effects of leadership style, human resource development and job discipline on personnel’s performance at Regional People Representative Secretariat, Central Sulawesi Province. Sample of this research involves 81 personnel at Regional People Representative Secretariat, Central Sulawesi Province which have been regression. Based on data analysis, it indicates regression equation Y=1,651 + 0,265X1 + 0,208X2 + 0,186X3. The result show that leadership style, human resource development and job discipline perform positive and significant effect on personnel’s performance. Determination test indicates that the value of adjusted R square is 0,623 which means that 62,30% personnel development and job discipline. Meanwhile, 37,70% is affected by other variables which are not investigated in this research.